BIM education for quality surveying students using REVIT tools: evaluating the knowledge, awareness and perception / Dr. Noor Akmal Adillah Ismail ... [et al.] - Baharuddin, Har Einur Azrin; Mohd Zaki, Zulkhairy Affandi; Mohamad Kamil, Abdul 'Izz; Ramli, Hazwani; Ismail, Noor Akmal Adillah (College of Built Environment, 2023)
The implementation of BIM has been proven to enhance the productivity and efficiency throughout the construction process in other countries such as United Kingdom, Singapore, Hong Kong (Building Research Levy, 2016)